Learning and mastering pharmaceutical calculations - Ferencz, Nicholas (Pharmacist) (American Society of Health-System Pharmacists, Inc., 2018)
A valuable supplement to any pharmacy math course or textbook, Learning and Mastering Pharmaceutical Calculations makes the process of sharpening critical calculation skills more efficient and effective for students and technicians at all levels of experience, as well as practitioners looking to refresh their skills. Written by Nicholas Ferencz, Pharm.D., Ph.D., this unique new workbook enhances the learning experience in several ways. Learners.